Unveiling island tourism in cape verde through online reviews - Oliveira, Cristina (2021)
Oliveira, C., Rita, P., & Moro, S. (2021). Unveiling island tourism in cape verde through online reviews. Sustainability (Switzerland), 13(15), 1-14. [8167]. https://doi.org/10.3390/su13158167